Effciency Concern under Asymmetric Information - Evguenia Winschel; Philipp Zahn (University of Mannheim, Department of Economics, 2012)
Experimental evidence from simple distribution games supports the view that some individuals have a concern for the effciency of allocations. This motive could be important for the implementation of economic policy proposals. In a typical lab experiment, however, individuals have much more information available than outside the lab. We conduct a lab experiment to test whether asymmetric information influences prosocial behavior in a simple non-strategic interaction. In our setting, a dictator has only limited knowledge about the benefits his prosocial action generates for a recipient. We find that a substantial share of subjects behaves proscially and a concern for effciency plays an important role. In our experiment the information asymmetry is actually effciency-enhancing as more subjects behave prosocially than under symmetric information.
urn:nbn:de:bsz:180-madoc-330056
Keywords: D82; C91; 330